Gestão sustentável de pessoas : contribuições para o desenvolvimento de uma universidade pública federal - Andrade, Fabiana de Cássia Ramos de Medeiros Fernandes Alves de (2023)
This research entitled “Sustainable People Management: contributions to the development of a federal public university” had the general objective of verifying how Sustainable People Management (GSP) practices are configured in a federal higher education institution (IFE), with special attention to the Environmental, Social and Governance (ESG) agenda, which presents itself as an essential tool to promote efficient public management. Thus, we sought to identify these practices; investigate their contributions to institutional development and verify the main barriers to their implementation in the field of public management and, specifically, at the Federal University of Paraíba (UFPB), the locus of the research. This is a study with a qualitative, empirical, exploratory approach that took as data sources official documents and websites, publications on institutional social networks and reports obtained through twelve interviews guided by a structured script, whose respondents were the Management Agents of People (AGP), present in the most diverse administrative units of the institution. The analysis of the content collected in the field was guided by the method proposed by Bardin (1977). As the main results achieved, it can be pointed out that the AGP perceive Sustainable People Management as a relevant and beneficial model for the institution. GSP is seen as a way to promote management practices that go beyond purely environmental results, considering aspects such as employee well-being and organizational sustainability. Furthermore, within the scope of institutionalized practices, it was possible to identify that the university adopted measures aimed at training and developing employees, aiming to improve their skills and competencies. Furthermore, there is a focus on promoting a healthy and inclusive work environment, which values diversity and the well-being of employees. However, there were some barriers to implementing this innovation in people management, such as the discontinuity of projects after a change of managers at central and local levels, institutional communication with low effectiveness regarding such practices, the seasonality of some practices, the lack of engagement on the part of some employees, the absence of specific training, with a vision of sustainability, for the training of employees, especially leaders. The results presented are intended to promote interaction with new research, managers and potential leaders of the public service, aiming to provide support for the formulation of a renewed perspective of the future and for the promotion of sustainable innovations in Public Management. Future research may focus on empirical studies on evaluations of PMS practices and on the governance of people management in Public Administration.